Designing of Business Performance Measurement Instruments of Notify Coffee With Balanced Scorecard - Fairuz Zalfa Shaumi; Aisyah Putri Hidayah; Aurelia Putri Denia; Laonewan Rezki Alhaq (International Journal of Entrepreneurship and Business Management, 2022)
SMEs are one of the sectors that provide many job opportunities in Indonesia. SME Coffee Shop is one of the SME sub-sectors that is experiencing growth in Indonesia. A performance improvement strategy is needed to maximize the performance of SMEs Coffee Shop in order to compete and develop the business. This paper aims to identify the aligment of the SMEs vision, mission, goals and target, create a strategy map, identify Key Performance Indicator, and develop business used Balanced Scorecard method of Notif Coffee. The object of this research is Notif Coffee which is one of Coffee Shop SMEs in West Java. This study used are primary data obtained by structured interview with Notif Coffee owner and secondary data in the form of literature studies. The data processing and analysis method is carried by Key Performance Indicator and Balanced Scorecard consisting four targets, namely finance, learning and growth, internal business, and customer. The research shows that Notif Coffee have many problem in internal business perspective because Key Performance Indicator shows that target is not achived. The result of this research using balanced scorecard analysis with four perspectives led by the learning and growth, followed by the customer perspective, the financial perspective, and internal perspective.